(untitled) (International Journal of Engineering and Computer Science, 2015)
Image pre-processing tool, created in Matlab, realizes many brightness transformations and local pre-processing methods. The proposed solutions focus on applying Neural Network Algorithm model for character recognition. The primary function of which is to retrieve in a character stored in memory, when an incomplete or noisy version of that character is presented. The idea is to create a theoretical and practical basis of preprocessing for character recognition using forward-feed neural networks. The Feed Forward Algorithm gives insight into the enter workings of a neural network; followed by the Back Propagation Algorithm which compromises Training and Testing. Character recognition is one of the most interesting and challenging research areas in the field of Image processing. English character recognition has been extensively studied in the last half century. Nowadays different methodologies are in widespread use for character recognition. Document verification, digital library, reading bank deposit slips, reading postal addresses, extracting information from cheques, data entry, applications for credit cards, health insurance, loans, tax forms etc. are application areas of digital document processing.